The in vitro and in vivo evaluations of newly formulated osteoprotegerin-chitosan gel in bone regeneration / Soher Nagi Mohammed Jayash - Soher Nagi, Mohammed Jayash (2017)
The receptor activator of nuclear factor kappa-B (RANK)/RANK ligand/osteoprotegerin (OPG) system plays a critical role in bone remodelling by regulating osteoclast formation and activity. OPG has been used systemically in the treatment of bone diseases that has many side effects. Therefore, in searching for more effective and safer treatment for bone diseases, we have investigated newly formulated OPG-chitosan complexes, which is prepared as a local application for its osteogenic potential to remediate bone defects. This study was designed to develop a new OPG-chitosan gel for bone tissue engineering applications and to evaluate the biocompatibility, sustained release ability and biodegradability of gel in vitro. The cytotoxicity of OPG in chitosan and its proliferation in vitro was evaluated using normal, human periodontal ligament (NHPL) fibroblast cell culture. The cytotoxicity of these combinations was compared by measuring cell survival with a tetrazolium salt reduction (MTT) assay. The cellular morphological changes were observed under an inverted microscope. A propidium iodide and acridine orange double-staining assay was used to evaluate the morphology and quantify the viable and nonviable cells. The present study also evaluated the effectiveness of new formulated OPG- chitosan gel in vivo. In this study, the OPG-chitosan gel was formulated using human OPG protein and three different molecular weights (MW) of water-soluble chitosan i.e. 10, 25 and 50 kDa. The physicochemical properties were determined using the fourier transform infra-Red (FTIR) spectroscopy, thermogravimetric analysis (TGA) and the differential scanning calorimetry (DSC). The formulation gel was subjected to protein release assay and biodegradability test. In vitro cytotoxicity test of OPG-chitosan gel was carried out on NHPL fibroblast and NH osteoblast using the Alamar blue (AB) assay. The morphology of fabricated OPG-chitosan gels and attachment of cells on the gel was observed and compared using scanning electron microscope (SEM). The osteogenic potential of the OPG-chitosan gel was evaluated in 18 female rabbits which involved creating critical-sized defects on the calvarial bone, filled with the OPG-chitosan gel and sacrificed at 6 and 12 weeks. This study showed that the OPG-chitosan gel showed more thermally stable material with biodegradability rate (28 days). Chitosan could withstand temperatures of 200 °C before decomposing. The OPG-chitosan gel water uptake exhibited similarity of the fluid contents percentage with those of living tissues. The gel was able to enhance a favorable condition for cell viability and tissue growth in vitro. The AB assay result revealed that the OPG-chitosan gel has no critical cytotoxic effect on fibroblast and osteoblast cells and a clear cell layer covering the entire outermost surface of the gel was observed by scanning electron microscopy at 72 hours of incubation. The in vivo results showed bone growth in the OPG-chitosan gel filled defects with the mean values that statistically higher than that of the control defects (unfilled defects) (p < 0.05). In a nutshell, the results have suggested the newly developed OPG-chitosan gel has the ability to extend the release pattern, support the growing of cells, specific degradation by lysozyme, and the effectiveness of OPG-chitosan gel in bone healing. It can be concluded that the OPG-chitosan gel has many characteristics beneficial to tissue engineering applications.